2016
DOI: 10.1515/rela-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processing of verbal quantifiers in the context of affirmative and negative sentences: A Croatian study

Abstract: Abstract Studies from English and German have found differences in the processing of affirmative and negative sentences. However, little attention has been given to quantifiers that form negations. A picture-sentence verification task was used to investigate the processing of different types of quantifiers in Croatian: universal quantifiers in affirmative sentences (e.g. all), non-universal quantifiers in compositional negations (e.g. not all), null quantifiers in negative conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As previous research has indicated (e.g. Ćoso & Bogunović, 2016;Kaup et al, 2007a), the differences in negation processing may not be ascribed only to the two-step processing, as described by Kaup et al (2005Kaup et al ( , 2007a. The role of different linguistic cues could also be significant.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…As previous research has indicated (e.g. Ćoso & Bogunović, 2016;Kaup et al, 2007a), the differences in negation processing may not be ascribed only to the two-step processing, as described by Kaup et al (2005Kaup et al ( , 2007a. The role of different linguistic cues could also be significant.…”
Section: Discussionmentioning
confidence: 78%
“…For example, Kaup et al (2007a) found that definite negations are processed faster compared with indefinite negations, suggesting that word order and negation type could affect the creation of a situational model from the sentence. Ćoso and Bogunović (2016) recently found a significant difference in the processing of same-polarity sentences with first-order quantifiers. Negative concord sentences with null quantifiers were processed faster and more accurately than sentences with disproportional and non-universal quantifiers.…”
Section: Negation Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…The one-step or two-step debate is additionally complexified by factors that are known to cause processing differences, such as language-specific structural cues in negation 15 18 . One such linguistic cue is negative concord 6 , 19 21 a type of negation that languages like English and Croatian tolerate differently. Negative concord is a linguistic feature where a sentence contains multiple negative elements, but they contribute to just one semantic negation 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%